Optimalisasi Layanan Konseling Melalui Manajemen Data dan Materi Panduan di MA YPP Babakan Jamanis Parigi - Yayu Nuraidah Solihat; Ai Siska Silvia; Halimatussa'diyah Halimatussa'diyah; Sesi Bandawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
The research aims to optimize counseling services at MA YPP Babakan Jamanis Parigi, both optimal in the quality of counseling services, and optimal in students' understanding and ability to overcome the problems they face. The method used in this research is a qualitative approach with data collection techniques through observation, interviews, documentation and literature study. The research results show that there is a mismatch in terms of data management and guidance materials, both in the form of providing personal books and information brochures needed to support counseling services. The benefit of this research is to improve the quality of education in the school by evaluating aspects of guidance and counseling, helping students deal with personal problems, and improving relationships between students, teachers and parents. It is hoped that this research can be a reference for other schools in improving their counseling services.